Acute Urinary Retention in a 47-month-old Girl Caused by the Giant Fecaloma - Park, Ji Sook; Park, Tae-Jin; Hwa, Jung Seok; Seo, Ji-Hyun; Park, Chan-Hoo; Youn, Hee-Shang (Pediatric gastroenterology, hepatology & nutrition, 2013)
We present a case of a 47-month-old female suffering from acute urinary bladder neck obstruction and bilateral hydronephrosis secondary to a fecaloma. Fecaloma is defined as an accumulation of inspissated feces in the colon or rectum giving the appearance of an abdominal mass. A fecaloma can be developed by diverse causes and the causes of the fecaloma in this case were septum reformation after the Duhamel procedure and long-term constipation. Chronic constipation is very common at outpatient clinic. However, acute urinary retention and voiding difficulty caused by fecaloma in the giant Duhamel pouch has never been reported in Korea. We would like to present our case with acute urinary retention due to a fecaloma and suggest that fecaloma might be considered as one of the causes for acute urinary retention, especially in cases with previous Duhamel operation for repair of Hischsprung disease.